2010
DOI: 10.1007/978-3-642-17572-5_22
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Formation and Price of Anarchy in Cournot Oligopolies

Abstract: Non-cooperative game theory purports that economic agents behave with little regard towards the negative externalities they impose on each other. Such behaviors generally lead to inefficient outcomes where the social welfare is bounded away from its optimal value. However, in practice, self-interested individuals explore the possibility of circumventing such negative externalities by forming coalitions. What sort of coalitions should we expect to arise? How do they affect the social welfare?We study these ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Another line of research offers stronger performance guarantees using specific learning algorithms that employ equilibrium selection (e.g., in distributed load balancing [Kleinberg et al 2011a], in general congestion games [Kleinberg et al 2009], in evolutionary linguistic systems [Fox et al 2012]). The importance of such results that go beyond the analysis of performance of Nash equilibria has also been stressed in recent work [Kleinberg et al 2011b;Piliouras and Shamma 2014;Immorlica et al 2010;Nadav and Piliouras 2010] where, for example, it has been shown that even in simple and well-studied games, the performance of natural learning dynamics can be arbitrarily better than the social welfare of even the best Nash equilibria. A mini-review of this literature can be found in Ligett and Piliouras [2011].…”
Section: Related Workmentioning
confidence: 99%
“…Another line of research offers stronger performance guarantees using specific learning algorithms that employ equilibrium selection (e.g., in distributed load balancing [Kleinberg et al 2011a], in general congestion games [Kleinberg et al 2009], in evolutionary linguistic systems [Fox et al 2012]). The importance of such results that go beyond the analysis of performance of Nash equilibria has also been stressed in recent work [Kleinberg et al 2011b;Piliouras and Shamma 2014;Immorlica et al 2010;Nadav and Piliouras 2010] where, for example, it has been shown that even in simple and well-studied games, the performance of natural learning dynamics can be arbitrarily better than the social welfare of even the best Nash equilibria. A mini-review of this literature can be found in Ligett and Piliouras [2011].…”
Section: Related Workmentioning
confidence: 99%
“…In a previous work [19], the author considered Cournot Competition on a network of firms and markets; however, assumed that inverse demand functions are linear and all the cost functions are quadratic function of the total production by the firm in all markets which is quite restrictive. Most of the results in other related works in Cournot Competition and Bertrand Network require linearity of the cost functions [3,20]. A brief summary of our results presented in three sections is given below.…”
Section: Results and Techniquesmentioning
confidence: 80%
“…The earliest and most well-known result in the area is the one on stable marriages by Gale and Shapley (Gale and Shapley 1962). Further works include (Aumann and Dreze 1974;Apt et al 2014;Banerjee, Konishi, and Sonmez 2001;Bogomolnaia and Jackson 2002;Chalkiadakis et al 2009;Feldman, Lewin-Eytan, and Naor 2012;Greenberg and Weber 1993;Hajdukova 2006;Hart and Kurz 1983;Immorlica, Markakis, and Piliouras 2010;Yi 1997).…”
Section: Related Workmentioning
confidence: 99%